Historical review of Citrus tristeza virus in Portugal - Nolasco G. (Citrus tristeza virus and Toxoptera citricidus: a serious threat to the Mediterranean citrus industry, 2009)
Most of the citrus production in Portugal is located in the Algarve region, in the south, which accounts for almost 70 percent of the national production. A boom of citrus planting occurred in the late 1980s with the introduction of modern varieties. This was accompanied by the introduction of CTV in the plant propagation material. Surveys for the virus and vectors started also at that time accompanied by the eradication of several foci of the disease. In parallel, works aiming at the molecular characterization of the virus were pursued. Up to the year 2000 most of the virus variants found in the orchards were similar to the Spanish predominant variant. Later the appearance of different variants became frequent. In 2005 new foci were detected in the north western part of the country in places where T. citricidus was present. With these new virus variants, the complete set of strains existing at worldwide level is now present in Portugal mainland.